PENERAPAN PEMBELAJARAN KOOPERATIF UNTUK MENINGKATKAN KETERAMPILAN SOSIAL DAN HASIL BELAJAR MATEMATIKA SISWA KELAS VII.3 SMP NEGERI 35 PEKANBARU - Syarifah Nur Siregar; Kartini ' (Jurnal Pendidikan, 2014)
This study is a descriptive study that aimed to gain an overview ofthe quality and improvement of students 'social skills and improving students'mathematics learning outcomes after cooperative learning. The experiment wasconducted in the odd semester of academic year 2013/2014. The subjects were 40students of class VII.3 SMPN 35 Pekanbaru consisting of 20 boys and 20 girls.Data collected through questionnaire distribution, observation, and test. Dataanalysis was performed using descriptive techniques. The results showed thatsocial skills of students in a category medium (89.55). If the terms of the fiveaspects of social skills, the social skills consecutive highest to lowest is self-management skills (3.18), the skills to relate to others (3.09), the skills ofexpression (3.07), skill abide by the rules (3.04), and academic skills (2.70).Social skills of students increased after the cooperative learning that is equal to0.027. If the terms of the categories of social skills, then there is a markedincrease with increasing the number of students at the high skill category of 11students (27.5%) before the cooperative learning to 14 students (35%) after thecooperative learning. Mathematics learning outcomes of students also increasedafter the cooperative learning that is equal to 0.068. Increasing students'mathematics learning outcomes also occur if the terms of achievement KKMmarked by the increasing number of students who achieve KKM before learningcooperative of 15 students (23%) to 23 students (57.5%) after the cooperativelearning. The results of this study indicate that the application of cooperativelearning can improve social skills and mathematic learning outcomes of classVII.3 SMPN 35 Pekanbaru.Key words: Cooperative learning, social skill, mathematic learning outcome